Relationship Between Occupation and The Incidence Of Condyloma Akuminata in The Skin And Genital Clinic of Dr. H. Abdul Moeloek General Hospital in Lampung Province For The Period 2018-2020 - Dinda Dwi Anjani; Eka Silvia; Abdurrohman Izzuddin; Arif Effendi (Fakultas Kedokteran Universitas Sriwijaya, 2021)
Sexually transmitted infections (STIs) are one of the causes of health, social and economic problems in many countries, it was reported that in the last 35 years the prevalence of Human papilloma virus infections worldwide continues to increase. Economic deprivation, low education, economic inequality, and economic-driven migration and mobility are all linked to the risk of transmitting STIs including condyloma acuminata. Determine the relationship between occupation and the incidence of condyloma acuminata in the skin and genital clinic of Dr. H. Abdul Moeloek in Lampung province for the period 2018-2020. Using an analytical observational study with a cross-sectional research design. Sampling using total sampling technique. Data collection by medical record respondents and analyzed using spearman correlation test. It was found that 102 respondents with the highest frequency of occupation were private workers, 33 people (32.4%). The spearman correlation test result obtained p=0,033 (p<0,05), which means that there is a significant relationship between occupation and incidence of condyloma acuminata in the skin and genital clinic in Dr. H. Abdul Moeloek in Lampung province.